Perception about the ‘opt out strategy’ for HIV testing and counselling among pregnant women attending antenatal clinic in Ibadan, Nigeria (2015)
Background: Opt out strategy was designed to improve uptake of HIV testing and counselling (HTC) services but only a fifth of the population utilise this service in Nigeria. This study was conducted to determine perception about the opt out strategy for HIV screening among pregnant women attending antenatal clinic in a secondary health facility in Ibadan, Nigeria where the opt out strategy was used for HIV screening. Methodology: Cross sectional study was conducted and systematic random sampling was used to recruit 500 pregnant women. Data regarding sociodemographic characteristics, general knowledge about HIV transmission, assessment of HIV screening services in the hospital and attitude towards HIV screening was obtained. Results: Mean age of respondents was 27.4 (SD±6.1) years, 86.8% were married and 79.2% had at least secondary school education. Overall, 69.2% had good knowledge about routes of HIV transmission. More than 90% reported that information received during the HTC session was understood. Only 41.8% reported adequate privacy during screening process while 20.4% felt they were forced to participate. Positive attitude towards HTC was seen in 72.0%. Higher education was associated with better knowledge of routes of HIV transmission (OR=3.8; 95%CI= -4.3-3.3) Being married or cohabiting with a partner (OR=3.7; 95% CI=16.8-0.8), having more than one sexual partner (OR=3.3; 95%CI=-3.7-2.97) and being HIV negative (OR=3.9; 95%CI=39.0-0.39) was associated with a positive attitude towards HIV screening. Conclusion: Inadequate privacy and patient's voluntariness were major complaints about opt out strategy for HTC. Improving privacy and stressing that screening is optional may improve general uptake of HTC when using the opt out strategy.